A Contextual Interpretation of the Secrets of Surah al-Fatiḥah in al-Ghazali's Jawāhir al-Qur'an - Nurjannah, Elina; Hadani, Abdullah; Muhammad Akhdan Muzakki (Universitas Ahmad Dahlan, 2024)
This study examines the contextual interpretation of Surah al-Fatihah in Jawāhir al-Qur’an, a work by al-Ghazali, through the lens of Abdullah Saeed’s contextual hermeneutics. Al-Ghazali’s approach to Surah al-Fatihah combines esoteric and philosophical dimensions, emphasizing its spiritual and transcendental messages. Unlike traditional interpretations, his thematic focus refrains from detailed grammatical analysis, instead highlighting its role as a reflection of a believer’s spiritual journey. Employing a qualitative and library research methodology, this study contextualizes al-Ghazali’s interpretations for modern relevance, particularly in addressing contemporary issues of servitude and obedience to Allah. The findings suggest that al-Ghazali’s model of exegesis, rooted in Sufi thought, offers a dynamic framework for reinterpreting Qur’anic messages to maintain their applicability in contemporary life.